On the first singularity for the Upsilon invariant of algebraic knots. (23rd February 2016) - Wang, Shida
Abstract : We show that the location of the first singularity of the Upsilon function of an algebraic knot is determined by the first term of its Puiseux characteristic sequence. In many cases, this gives better bounds than the tau invariant on the genus of a cobordism between algebraic knots.